Experiences of UK patients with hepatitis C virus infection accessing phlebotomy: A qualitative analysis. (11th December 2014) - Clements, Amanda; Grose, Jane; Skirton, Heather
Abstract This study provides an understanding of the experiences and perceptions of phlebotomy in people with infection who have venous damage related to injecting drug use with the aim of improving their care. Narrative interviews were conducted with 10 attendees of a phlebotomy service within an acute Trust in the south–west of England. The participants had hepatitis C infection and poor venous access due to current or former drug use. Interview audiotapes were analyzed, and the themes – conflict, emotional responses, the patient as expert, and offering solutions – were identified. In the context of this study, we discuss the difficulties associated with phlebotomy, which might explain why individuals with hepatitis C infection and venous damage disengage from health services and are less likely to undertake antiviral treatment. This research adds to the literature on phlebotomy for vulnerable groups, and recommends hepatitis C virus clinics within drug agencies, the need to review training and policy, and the development of "phlebotomy passports" to enable continuity of care between services.